Astrocyte-Derived Pleiotrophin Mitigates Late-Stage Autoimmune CNS Inflammation - Linnerbauer, Mathias; Lößlein, Lena; Farrenkopf, Daniel; Vandrey, Oliver; Tsaktanis, Thanos; Naumann, Ulrike; Rothhammer, Veit (Frontiers in Immunology, 2022)
Astrocytes are the most abundant glial cells in the central nervous system (CNS) with the capacity to sense and react to injury and inflammatory events. While it has been widely documented that astrocytes can exert tissue-degenerative functions, less is known about their protective and disease-limiting roles. Here, we report the upregulation of pleiotrophin (PTN) by mouse and human astrocytes in multiple sclerosis (MS) and its preclinical model experimental autoimmune encephalomyelitis (EAE). Using CRISPR-Cas9-based genetic perturbation systems, we demonstrate in vivo that astrocyte-derived PTN is critical for the recovery phase of EAE and limits chronic CNS inflammation. PTN reduces pro-inflammatory signaling in astrocytes and microglia and promotes neuronal survival following inflammatory challenge. Finally, we show that intranasal administration of PTN during the late phase of EAE successfully reduces disease severity, making it a potential therapeutic candidate for the treatment of progressive MS, for which existing therapies are limited.